Find the difference quotient of \( f \), that is, find \( \frac{f(x+h)-f(x)}{h}, h \neq 0 \), for the following function. \( f(x)=-4 x+6 \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
The Deep Dive
To find the difference quotient, we first need to compute \( f(x+h) \). Given the function \( f(x) = -4x + 6 \): 1. Calculate \( f(x+h) \): \[ f(x+h) = -4(x+h) + 6 = -4x - 4h + 6 \] 2. Now, plug this back into the difference quotient formula: \[ \frac{f(x+h) - f(x)}{h} = \frac{(-4x - 4h + 6) - (-4x + 6)}{h} \] 3. Simplify the numerator: \[ = \frac{-4x - 4h + 6 + 4x - 6}{h} = \frac{-4h}{h} \] 4. Finally, since \( h \neq 0 \), we can cancel \( h \) to find: \[ = -4 \] So, the difference quotient for the function \( f(x) = -4x + 6 \) is \( -4 \).